Modeling early haematologic adverse events in conformal and intensity-modulated pelvic radiotherapy in anal cancer. Issue 2 (November 2015) - Robinson, Maxwell; Sabbagh, Ahmed; Muirhead, Rebecca; Durrant, Lisa; Van den Heuvel, Frank; Hawkins, Maria
Abstract: Background and purpose: To determine if there are differences between dose to pelvic bone marrow (PBM) using intensity modulated radiotherapy (IMRT) under UK guidance versus conformal radiotherapy (CRT) per ACT II protocol and if differences translate to rates of early haematological adverse events grade 3 or greater (HT3+). Methods and materials: Two groups of 20+ patients, treated under IMRT and CRT regimes respectively, were identified. All patients underwent weekly blood cell count: haemoglobin (HgB), white cell count (WCC), absolute neutrophil count (ANC) and platelets (plats). Percent volume of PBM and sub structures receiving 5–25 Gy were tested for statistical significance. Regression models were used to test for correlation to blood counts. NTCP modeling was also performed. Results: PMB dose metrics showed a significant increase in the IMRT group. Regression analysis showed iliac and lumbosacral PBM dose metrics to associate with reduced nadir ANC and WCC. NTCP at HT3+ was 0.13 using IMRT relative to 0.07 using CRT ( p  < 0.05). Conclusion: Whilst this is a relatively small retrospective study and lacks information on the distribution of active PBM, IMRT treatment has been shown to significantly increase PMB irradiation. PBM dose metrics have been shown to be predictive of WCC and ANC suppression. NTCP modeling predicts much high risk of HT3+. Paradoxically, actual rates of HT3+ were comparable suggesting that differences in the distributions of dose metrics maybe a significant factor and/or that there are insufficiency in the NTCP modeling.